2009
DOI: 10.1111/j.1524-475x.2009.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effect of hyperbaric oxygen on wound angiogenesis and epithelialization

Abstract: Hyperbaric oxygen (HBO) therapy is increasingly being used in different areas of medical practice. While demonstrated to be effective in several settings, its mechanism of action is not well understood. In the present study, we determined the effects of HBO on wound epithelialization and neovascularization in an in vivo hairless mouse ear "impaired" wound model. To impair wound healing, macrophages were depleted by pretreatment with iota-carrageenan. Wound epithelialization and neovascularization were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 30 publications
1
48
0
2
Order By: Relevance
“…Indeed, animals exposed to HBO exhibited skin revascularization in the lesion site which could facilitate glucantime delivery. Previous reports have shown in wound mouse models 27,31 , transplanted rats 31 , and rat liver after partial hepatectomy 17 that neovascularization is increased in animals exposed to HBO. To analyze whether the therapies induce immune responses, INF-γ and IL-4 levels were measured.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, animals exposed to HBO exhibited skin revascularization in the lesion site which could facilitate glucantime delivery. Previous reports have shown in wound mouse models 27,31 , transplanted rats 31 , and rat liver after partial hepatectomy 17 that neovascularization is increased in animals exposed to HBO. To analyze whether the therapies induce immune responses, INF-γ and IL-4 levels were measured.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, HBOT is widely used for the treatment of diabetic ulcers (Duzgun et al 2008;Liu and Velazquez 2008;Ong 2008;Thackham et al 2008;Efrati et al 2009), an application that will only increase as the population ages. One way HBOT acts to enhance chronic wound healing is by stimulating angiogenesis (Ren et al 2008;Milovanova et al 2009;Sander et al 2009;Yuan et al 2009). The tissue responsible for angiogenesis, the vascular endothelium, has been the topic of several studies to determine the mechanisms of the beneficial effects of HBO.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, in this study, it was concluded that part of the positive effect of wound outcome was due to the release of metalloproteinases [26]. This is not inconsistent with many published reports because their data showed that MMP-9 was elevated significantly in the impaired healing group.…”
Section: Discussionmentioning
confidence: 52%